Answer:the third option is the correct answer
Explanation:
The given system of linear equations is expressed as
y – 3x = –2 - - - - - - - - - - - -1
y = 4 - - - - - - - - - - - - - 2
The first step is to substitute equation 1 into equation 2. It becomes
4 – 3x = –2
Subtracting 4 from the left hand side and the right hand side of the equation, it becomes
4 - 4 - 3x = –2 - 4
- 3x = - 6
Dividing the left hand side and the right hand side of the equation by - 3, it becomes
- 3x/ - 3 = - 6/ - 3
x = 2
(2, 4)